Virtual reality is only mildly effective in improving forest conservation behaviors - Sanchayan Banerjee; Alipio Ferreira (Scientific Reports)
Abstract Virtual Reality (VR) enables immersive experiences that can enhance awareness about environmental problems. We measure the effectiveness of VR versus 2D in an environmental campaign using a field experiment in Brazil. 617 passers-by at a mall were randomly assigned to watch a video clip about the Amazon Forest through VR or a traditional 2D device, with some being randomly interviewed before watching the movie (control group). We find that both the 2D and VR interventions increase individuals’ propensity to (i) contribute to an Amazonian humanitarian campaign, (ii) share contact information, (iii) interact with a conservation campaign, and (iv) state pro-conservation opinions. We find no additional impact of VR compared to 2D, but VR participants were more likely to engage with pro-conservation content online 3 months later. Our findings provide cautionary evidence about the additional potential of using immersive technologies, like VR, to improve conservation behaviors compared to 2D methods.